TENELIGLIPTIN – THE NEWEST DPP4 INHIBITOR - DR. MAYURESH KIRAN,; DR. H.B. CHANDALIA,; DR. PRAMILA YADAV, (International Journal of Pharma and Bio Sciences, 2017)
Teneligliptin is the newest DPP4 inhibitor approved by the regulatory authority for the treatment of Diabetes mellitus. Teneligliptin [TEN20], is approved in Japan, India, Korea, Argentina and currently undergoing Phase I trials in the USA and Phase II trials in Europe for the treatment ofT2DM. Teneligliptin scores over other ‘gliptins’ in being more economical and with better efficacy to control blood glucose and HbA1C levels. Teneligliptin additionally offers other pharmacological advantages like longer half-life, lesser IC50 value, tight and extensive binding to the DPP4 enzyme. Teneligliptin has been studies extensively for its safety and efficacy in various clinical trials conducted internationally. Teneligliptin has sufficient and adequate clinical data to prove itself as monotherapy and combination therapy with other Anti-Diabetic agents. No dose adjustment is requires in renal failure but certain studies included dose reduction in mild to moderate hepatic failure. Certain clinical trials have demonstrated cardio-protective effects of teneligliptin in T2DM patients with increase in serum adiponectin levels. It is safe and well tolerated, also weight neutral, have low risk of Hypoglycaemia and are equally efficacious with rare side effects compared to other gliptins. This review article comprehensively documents the available clinical and pharmacological data for Teneligliptin in the treatment of Diabetes mellitus.